2019
DOI: 10.15241/jrj.9.1.67
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of African American Mothers Raising Sons in the Context of #BlackLivesMatter

Abstract: A gap exists in the counseling profession between research and practice. Community-based participatory research (CBPR) is one approach that could reduce this gap. The CBPR framework can serve as an additional tool for translating research findings into practical interventions for communities and counseling practitioners. Stronger community partnerships between researchers and practitioners will further improve treatment for our clients. The purpose of this study was to develop competencies that would provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In accordance with the examination of the BA men's psychosocial experience within its environmental context, the code underlying the concept of empathic isolation is particularly meaningful. Empathic isolation has been defined as a lack of empathy from others regarding lived experiences, in this case racial injustice (Joe et al, 2019). As it pertained to empathic isolation Participant DC commented, "They don't empathize or sympathize with us at all-we always at the bottom of the barrel."…”
Section: Racial Pandemic Black Male Experiencementioning
confidence: 99%
“…In accordance with the examination of the BA men's psychosocial experience within its environmental context, the code underlying the concept of empathic isolation is particularly meaningful. Empathic isolation has been defined as a lack of empathy from others regarding lived experiences, in this case racial injustice (Joe et al, 2019). As it pertained to empathic isolation Participant DC commented, "They don't empathize or sympathize with us at all-we always at the bottom of the barrel."…”
Section: Racial Pandemic Black Male Experiencementioning
confidence: 99%
“…Furthermore, police brutality is a psychosocial stressor that can play a huge role in affecting Black mothers’ lives. Black mothers experience a gendered racial vulnerability by often being responsible for teaching their children how to respond to police violence in the “police talk” [ 35 ], which can cause psychological distress and physical manifestations of stress [ 36 ]. Police brutality and other forms of structural racism can also take a toll on Black mothers, including those in the workplace, as anticipated negative police-youth encounters have been linked to depressive symptoms among pregnant Black women [ 37 , 38 ].…”
Section: Police Brutality Social Unrest and Political Turmoilmentioning
confidence: 99%
“…Next, a qualitative study of African American adolescents by Staggers‐Hakim (2016) found that participants held a sense of connection to nationally recognized cases of UPV and developed beliefs that African American men experience discrimination from law enforcement officers, should fear law enforcement, should anticipate being racially profiled, and need to exercise caution to prevent harm. Last, a study by Joe et al (2019) found that African American mothers experience psychological distress, develop physical symptoms, exhibit hypervigilance in parenting, and experience isolation while raising their sons in the midst of vicarious exposure to UPV.…”
Section: Impact and Mental Health Implication Of Upvmentioning
confidence: 99%